2015
DOI: 10.1155/2015/345835
|View full text |Cite
|
Sign up to set email alerts
|

Are There Benefits from Teaching Yoga at Schools? A Systematic Review of Randomized Control Trials of Yoga-Based Interventions

Abstract: Introduction. Yoga is a holistic system of varied mind-body practices that can be used to improve mental and physical health and it has been utilized in a variety of contexts and situations. Educators and schools are looking to include yoga as a cost-effective, evidence-based component of urgently needed wellness programs for their students. Objectives. The primary goal of this study was to systematically examine the available literature for yoga interventions exclusively in school settings, exploring the evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 54 publications
(80 reference statements)
4
59
0
3
Order By: Relevance
“…In a grade school study, a literature search revealed nine RCTs on yoga from the years 1982e2014 [13]. The results suggested that the grade school children experienced reduced tension and anxiety and improved self-esteem and mood following yoga.…”
Section: Grade School Studentsmentioning
confidence: 99%
“…In a grade school study, a literature search revealed nine RCTs on yoga from the years 1982e2014 [13]. The results suggested that the grade school children experienced reduced tension and anxiety and improved self-esteem and mood following yoga.…”
Section: Grade School Studentsmentioning
confidence: 99%
“…Similarly, Ferreira‐Vorkapic et al . recently conducted a systematic review of randomized controlled trials of school‐based yoga interventions, in which they identified 48 published studies, nine of which were randomized controlled trials that met their inclusion criteria.…”
Section: Review Of Research On School‐based Yoga Interventionsmentioning
confidence: 99%
“…Yoga is being increasingly taught in school settings as a strategy to enhance student health, well-being, and performance (Butzer et al 2015), with systematic analyses (Ferreira-Vorkapic et al 2015; Serwacki and Cook-Cottone 2012) and narrative reviews (Butzer et al 2016; Khalsa and Butzer 2016) revealing preliminary evidence for the benefits of yoga in schools. For example, Khalsa and Butzer (2016) conducted a bibliometric analysis of research on school-based yoga programs and identified 47 studies, most of which reported beneficial effects of school-based yoga on student outcomes such as psychological well-being, academic performance, and health-related measures.…”
Section: Introductionmentioning
confidence: 99%